Looking Back, Looking Forward - Riessman, Catherine Kohler (Narrative Works)

(untitled) (Centre for Interdisciplinary Research on Narrative, St. Thomas University, 2020)
Responding to the honor of the festschrift, I name and honour those who guided me, especially my mentor, Elliot Mishler. I describe a path from initial fascination with the idea of a “story” to my subsequent work that expanded the study of narrative in the human sciences. Efforts to understand how individuals interpreted—made sense of—events and situations that had interrupted their lives led me to discoveries about narrative form, apparent only after close textual interactional analysis. Recently, the appeal of narrative has mushroomed; I urge scholars not to lose sight of features that distinguish it from other forms of discourse.